Boars for breeding: a study of methods of evaluation used at testing stations - Ettala, Elsi ([E. Ettala], 1973)
Selostus: Karjujen koeasematestauksen tuloksellisuudesta.
Keywords: karjut; jalostus; kotieläinjalostus; sika; jälkeläiset; perinnöllisyys